If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 8 = x + 11 Reorder the terms: 8 + 2x = x + 11 Reorder the terms: 8 + 2x = 11 + x Solving 8 + 2x = 11 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8 + 2x + -1x = 11 + x + -1x Combine like terms: 2x + -1x = 1x 8 + 1x = 11 + x + -1x Combine like terms: x + -1x = 0 8 + 1x = 11 + 0 8 + 1x = 11 Add '-8' to each side of the equation. 8 + -8 + 1x = 11 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 11 + -8 1x = 11 + -8 Combine like terms: 11 + -8 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| X=-0.5x+3 | | -7(2t+8)=-126 | | r+(-016)=0.37 | | 5(f-1)=-25 | | (7a^3-2a^2-4a+9)+(3a+6)-(-a^2-a+3)= | | 14x+18y=63 | | -9(T-2)-(t+3)=2 | | x+44=4x+17 | | 2(3x+4)=2x+1 | | 8(s-7)=-92 | | 3x-4=x-10 | | 3x+4+x+20=180 | | 8x+6y=120 | | S^2-s-12=0 | | 8(2l+2)=32 | | 4x+(-7x)=9 | | 3(a-5)=54 | | -3x+7+2x=5 | | 8x-4+12+6x=180 | | 50x^2+40x-45=0 | | 48-92+67=y | | 25x-4x+y=36 | | (2x-5)(3x^2+3x-1)= | | p-4/11=29/11 | | (x+8)-x-(5-6)=15 | | X^3-5x-14x=0 | | 5c-(-32)=87 | | 4-6x=3y | | 3w^2-12w+16=0 | | 9-3x+5=2x+4 | | 10+5=515 | | 4n+2=7n-13 |